INNOVATIVE WAYS OF ORGANIZING ASSESSMENT ACTIVITIES IN THE DIGITAL ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: This article examines innovative ways of organizing valuation activities in the digital economy. The article also examines the issues of forming and developing valuation activities as a condition for ensuring the civilized regulation and transparency of digital economic relations in the context of the formation of a digital economy in the economy of our republic, the expansion of the processes of privatization, denationalization, structural transformation and corporatization of enterprises, the attraction of foreign capital, the expansion of various types of operations carried out with property and non-property rights, the development of market mechanisms of economic management.